Outward FDI, merchandise and service trade: evidence from Singapore - Wong, Koi Nyen *; Goh, Soo Khoon (Taylor & Francis, 2013)
This paper aims to explore the causality pattern between outward foreign direct investment (OFDI) and major external trade components (i.e. exports and imports of merchandise as well as services) using Singapore as a case study, since it is one of the largest outward investors in the Asian region and it is overtly trade-dependent. The findings reveal that there is evidence of an OFDI-led trade hypothesis, particularly with regard to merchandise exports and imports, which is an indication OFDI opens important channels for intra-firm trade activities, home country sourcing and backward integration. However, there is no evidence of causality relationships between Singapore’s OFDI and services trade because the purpose of such services is mainly to provide a market presence in the consuming country. As such, Singaporean multinationals are likely to outsource their services either from the host country services sector or from their own services-supporting subsidiaries that have been relocated abroad. The present study provides implications for policy formulation to strengthen OFDI-services trade linkages.